Electrical interconnection system for heating eye-shield - O'Malley, V.; Cornelius, J. C. (2018)
Bus bar electrical interconnection system adapted for use with an irregularly - shaped eye - shield and adapted for inter connection with leads from a battery to power a heating element affixed to the eye - shield, the interconnection system having bus bars, each bus bar adapted for connection with a lead from the battery, one or more of the bus bars having at least one protrusion, or alternatively a recession, providing at least one partial contact area of the bus bars, together with alternatively provided painted contact pads on the heating element, and at least one peripheral member securing inter connection of the partial contact surface area of the bus bars with the heating element, for providing customized heating of the heating element depending upon the number and extent of partial contact areas for customized heating to prevent fogging of the eye - shield.